Intergenerational transmission of neighbourhood poverty in Sweden: An innovative analysis of individual neighbourhood histories - Maarten van Ham; Lina Hedman; David Manley; Rory Coulter (Institute for the Study of Labor (IZA), 2012)
The extent to which socioeconomic (dis)advantage is transmitted between generations is receiving increasing attention from academics and policymakers. However, few studies have investigated whether there is a spatial dimension to this intergenerational transmission of (dis)advantage. Drawing upon the concept of a neighbourhood biography, this study contends that there are links between the places individuals live in with their parents and their subsequent neighbourhood experiences as independent adults. Using individual level register data tracking the whole Swedish population from 1990 to 2008, and bespoke neighbourhoods, this study is the first to use innovative sequencing techniques to construct individual neighbourhood histories. Through visualisation methods and ordered logit models, we demonstrate that the socioeconomic composition of the neighbourhood children lived in before they left the parental home is strongly related to the status of the neighbourhood they live in 5, 12 and 18 years later. Children living with their parents in high poverty concentration neighbourhoods are very likely to end up in similar neighbourhoods much later in life. The parental neighbourhood is also important in predicting the cumulative exposure to poverty concentration neighbourhoods over a long period of early adulthood. Ethnic minorities were found to have the longest cumulative exposure to poverty concentration neighbourhoods. These findings imply that for some groups, disadvantage is both inherited and highly persistent.
urn:nbn:de:101:1-201301213769
Keywords: I30; J60; R23; 330; intergenerational transmission; neighbourhood poverty; neighbourhood histories; sequence analysis; Sweden; Wohnstandortwahl; Nachbarschaft; Soziale Schicht; Generationenbeziehungen; Schweden